(untitled) (Annals of Medical Research, 2021)
Aim: Laparoscopic cholecystectomy is a widely performed technique worldwide. The use of laparoscopic threaded holders for this is routine but takes a lot of time and may tear the gallbladder. There are no wide-mouthed and short endoscopic instruments that can be used for removing the gallbladder without perforation. We look at gallbladder removal methods that are quick and do not involve damage at the end of laparoscopic cholecystectomy.Materials and Methods: This prospective study was conducted on 30 laparoscopic cholecystectomy patients divided into two equal groups, one employing conventional laparoscopic cholecystectomy (CLC) and the other using a sponge holding forceps (SHF) (n=15, both groups) to demonstrate the effectiveness of our management. In the CLC group, the number of male patients was two (13.3 %) and female patients 13 (86.7%); in the SHF group, number of male patients was six (40%) and female patients nine (60%). When we compared the results statistically for bladder removal time, total operation time, gallbladder perforation, and wound infection, the p values were found to be 0.016, 0.182, 0.169, and 1, respectively.Results: Thirty patients were analyzed. The SHF group showed significantly better results than the CLC group for gallbladder removal time and better although not significantly better results for perforation of bladder, while there was no difference between the groups for wound infection.Conclusion: Removing the gallbladder with an SHF significantly shortens the duration of removal and also reduces perforations as compared to CLC.Keywords: Laparoscopic Cholecystectomy; Forceps; Techniques.